THE SYSTEMIC ELEMENT OF INFLAMMATION IN ASTHMA COMORBID WITH HYPERTENSION DISEASE - T. N. Zaripova; I. I. Antipova; I. N. Smirnova (Кардиоваскулярная терапия и профилактика)
Aim. Evaluation of the severity of inflammation at systemic level and its relation with clinical picture, lipid parameters, lipid peroxidation and antioxidant system (LP-AS) in bronchial asthma (BA) patients with comorbid arterial hypertension (AH).Material and methods. Totally, 77 BA and AH patients included. Comparison groups included 53 BA and 52 AH monovariants. Clinical state assessed, biochemical and immunological parameters characterizing the activeness of inflammation, lipid metabolism, LP-AS system.Results. The severity of systemic inflammation is closely related to local bronchial inflammation, especially with comorbid AH. The relation of systemic inflammatory reaction is proved with the control ability of BA, as with lipid metabolism disorders and LP-AS system.Conclusion. The assessed comorbid pathology is characterized by the existence of local and systemic inflammation forming a “vicious circle” of the antioxidation activity, lipid disorders and endothelial dysfunction.